The Responses of Mouse Preimplantation Embryos to Leptin In Vitro in a Transgenerational Model for Obesity - Kšiňanová, Martina; Čikoš, Štefan; Babel’ová, Janka; Šefčíková, Zuzana; Špirková, Alexandra; Koppel, Juraj; Fabian, Dušan (Frontiers in Endocrinology, 2017)
The aim of the present study was to test the hypothesis that leptin can directly mediate the negative effect of maternal obesity on preimplantation embryos. As previously shown, maternal obesity retards early embryonic development in vivo and increases the incidence of apoptosis in blastocysts. When two-cell embryos isolated from control and obese mice were transferred to identical (leptin-free) conditions in vitro, no differences in any growth or quality parameters were recorded, including apoptosis incidence in blastocysts. Embryos isolated from control mice responded to transfer to environments with a high concentration of leptin (10 ng/ml) with a significant increase in arrest at the first or subsequent cell cycle. However, the majority of non-arrested embryos developed into blastocysts, showing morphology comparable to those cultured in the leptin-free group. On the other hand, the exposure of embryos isolated from obese mice to high leptin concentration in vitro did not retard their development. Furthermore, these embryos developed into blastocysts, showing a lower incidence of apoptosis. In vivo-developed blastocysts recovered from obese mice showed elevated expression levels of the pro-apoptotic gene BAX and the insulin-responsive glucose transporter gene SLC2A4. In conclusion, elevated leptin levels have both positive and negative effects on preimplantation embryo development in vitro, a response that likely depends on the body condition of the embryo donor. Moreover, these results suggest that leptin acts as a survival factor rather than an apoptotic inductor in embryonic cells. Since no elevations in the expression of the leptin receptor gene (LEPR) or fat metabolism-associated genes (PLIN2, SLC27A4) were recorded in blastocysts recovered from obese mice, the role of leptin in mediating the effects of obesity on embryos at the peripheral level is likely lower than expected.